Tratamento de superfícies em peças de titânio de grau medicinal - Ludmila Goncalves de Oliveira (2015)
The coatings of metal surfaces of implants with bioactive materials arean alternative in the search for materials for bone regeneration with long life useful, quickly fixation and lower bounce. In this research, parts of commercial pure titanium grade 2, with a treatment similar to the commercial surface, are covered by bioglasses system (SiO2)0.80(P2O5)0.04(CaO)0.16 at room temperature, and subjectedto two different thermal treatments, 37°C,called BGTi37 and 600°C, called BGTi600, and compared to commercial titanium.Chemical analysis of the material was performed by spectroscopy in theinfrared region for Fouriers Transform with diffuse reflectance, diffraction X rays spectroscopy, X rays energy dispersive, X rays photoelectron spectroscopy and zeta potential. It was possible to determine the composition, the important functional groups related to bioactivity, and adherence of the formed materials, surface chemical characteristics, isoelectric point and the morphology of the samples. Theadherence of the film to the substrate was determined by ABNT MB 985, getting the GR 0 for formed materials. The morphology, thickness and roughness were determined by scanning electron microscopy and atomic force microscopy. They were obtained porous materials with a thickness and roughness appropriate to your application. The interference of the formation of oxides on the morphology andthickness was also investigated. The bioactivity of the materials of the substrate, was determined by the kinetics of the formation of carbonated apatite in simulated body fluid, KOKUBO following the method reported by spectroscopy in the infrared region for Fouriers Transform with diffuse reflectance, diffraction X rays spectroscopy and X rays photoelectron spectroscopy, with which it was possible to determine the calciumphosphates formed; by cell viability; alkaline phosphatase; and colonization in vitro on the surface of the material. The results showed the feasibility of using the materials as bioglass and titanium bone implants.